Intelligent learning infrastructure for knowledge intensive organizations a semantic web perspective - Lytras, Miltiadis D. 1973-; Naeve, Ambjorn (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2005)
In the context of Knowledge Society, the convergence of knowledge and learning management is a critical milestone. This book provides state-of-the-art knowledge through a balanced theoretical and technological discussion. The semantic web perspective helps reader to understand the new era of intelligent learning infrastructures in knowledge intensive organizations. Knowledge management, learning management, e-collaboration, intelligent tutoring and learning systems, ontologies, semantic web technologies, corporate learning, integrative knowledge portals, distributed knowledge and learning repositories, peer-to-peer technologies are discussed in a holistic way providing a reference book for the research area